The Codes of Advertising / Fetishism and the Political Economy of Meaning in the Consumer Society - Jhally Sut (Rouledge, 1990)
This book examines the commercial speech of advertising as a cultural phenomenon whose social significance far exceeds its economic influence. Acknowledgements, Preface, Introduction: Fundamentals and Starting Points, The Fetihism of Commodities: Marxism and Anthropology and Psychoanalysis, The Valorization of Consciousness: The Political Economy of Symbolism, The Codes of the Audience, Advertising Codes and Fetishism: An Empirical Study, Conclusion: Advertising and Religion and the Mediation of Meaning, Bibliography, Index.